2019
DOI: 10.31258/jnat.17.2.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxydant Extract of Endophytic Fungi Fusarium oxysporum LBKURCC41

Abstract: Fusarium oxysporum LBKURCC41 is one of endophyte fungi which is able to produce secondary metabolites. The purpose of this research was to discover an antioxidant agent from F. oxysporum LBKURCC41extract that was fermented in Huang medium for 15 d with of corn and potato with particle size of 80 mesh as carbon sources. The ethyl acetate extract from the cultured medium showed four dominant component with retentiont time of 3.24, 3.44, 17.02 and 18.889 min. The F. oxysporum LBKURCC41 extract containing compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…can increase the resistance of tomato plants because it produces secondary metabolites that act as antioxidants. According to Marlinda et al (2019), secondary metabolites, ethyl acetate in the endophytic fungus Fusarium sp. can act as antibacterials.…”
Section: Resultsmentioning
confidence: 99%
“…can increase the resistance of tomato plants because it produces secondary metabolites that act as antioxidants. According to Marlinda et al (2019), secondary metabolites, ethyl acetate in the endophytic fungus Fusarium sp. can act as antibacterials.…”
Section: Resultsmentioning
confidence: 99%
“…that have weak potential may need more time incubation to produce the compounds and that do not show antibacterial potential in S. aureus may have other potential compounds. Several studies have shown that endophytic microbes can produce antifungal substances (Souza, et al, 2014), antioxidants (Marlinda et al, 2019), anticancer, antivirus, insecticide (Lodewyckx, et al, 2002), and IAA hormone (Yarnaliza et al, 2010) Based on its effectiveness, the antibacterial activity of endophytic bacteria from the roots of the Purwoceng (P. pruatjan Molk.) was categorized as a bacteriostatic group because it can inhibit the growth S. aureus that was used.…”
Section: Discussionmentioning
confidence: 99%